Strawson contra Strawson: Moral Responsibility and Semi-Compatibilism - Chen, Melvin (2016)
This paper addresses the Basic Argument in favour of incompatibilism, both in its Strawsonian form and in its weakened form (the CDA). After examining the worries raised by this argument, I will defend a version of semi-compatibilism that is motivated by a narrative theory of the self, arguing that moral responsibility is possible even if the thesis of determinism is taken to be incompatible with the thesis of freedom of will. The semi-compatibilist argument that I provide lowers the standard of proof, stops the regress of causes, finds a buck-stopper in the form of a self who can be held morally responsible for a choice or an action, and avoids committing the Strawsonian fallacy of circular reasoning by not setting impossible demands on moral responsibility.